Constitutional principles of EU external relations - Baere, G. de. (Oxford : Oxford University Press, 2008)
This text explores how foreign policy fits within the complex constitutional structure of the EU, providing both an analysis of the constitutional reality of EU foreign policy and a theoretical analysis suggesting possibilities for reform.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Constitutional law -- European Union countries; European Union countries -- Foreign relations -- Law and legislation